Unusual long survival despite severe lung disease of a child with biallelic loss of function mutations in ABCA-3. (2018) - El Boustany, P.; Epaud, R.; Grosse, C.; Barriere, F.; Grimont-Rolland, E.; Carsin, A.; Dubus, J.C.
Abstract: Homozygous or compound heterozygous for frameshift or nonsense mutations in the ATP–binding cassette transporter A3 (ABCA3) is associated with neonatal respiratory failure and death within the first year of life without lung transplantation. We report the case of a newborn baby girl who developed severe respiratory distress soon after birth. She was diagnosed with compound heterozygous frameshift mutation of the ABCA3 gene. Despite extensive treatment (intravenous corticosteroids pulse therapy, oral corticosteroids, azithromycin, and hydroxychloroquine), she developed chronic respiratory failure. As the parents refused cardio-pulmonary transplantation and couldn't resolve to an accompaniment of end of life, a tracheostomy was performed resulting in continuous mechanical ventilation. A neurodevelopmental delay and an overall muscular dystrophy were noted. At the age of 5 years, after 2 episodes of pneumothorax, the patient died from severe respiratory failure. To our knowledge, this was the first case of a child with compound heterozygous frameshift mutation who posed such an ethical dilemma with a patient surviving till the age of five years.